Instrumentalização da língua espanhola do Uruguai: um estudo discursivo do diccionario del español del Uruguay - Branco, Natieli Luiza (2019)
In this paper, we aim to investigate the functioning of the Diccionario del español del Uruguay (DEU), of the Uruguayan National Academy of Letters, in its first edition published in 2011, and, with this, to understand the process of constitution of this work and its importance for the instrumentalization of the Spanish language of Uruguay. To carry out this research, we will use the dictionary as a discursive object and as a linguistic instrument, in accordance with the theoretical and methodological principles of the Analysis of Discourse of French line in articulation with the History of Linguistic Ideas and, from this, our analytical gesture turns to the introductory texts and entries of this dictionary. The first act of interpretation is to establish the theoretical movements between language, subject and history in order to apprehend the discourse of the dictionary, as well as to explore the different looks at it through lexicography, in order to understand the process of Hispanic-American and Uruguayan dictionarization. The second act of interpretation is to check the functioning of language in the constitution the notion of the nation state and how it marked the process of colonization and decolonization in the language language tools to understand the linguistic heterogeneity. The third act of interpretation is to verify the production conditions that circumscribe this dictionary: how the DEU relates to the network of senses and dictionaries to which it belongs. The results of the analyzes indicate that, in their introductory texts, the dictionary subjects demonstrate that it is a contrastive dictionary: contrasts with the Spanish language present in the Diccionario de la lengua española (DLE) of the Royal Spanish Academy and there is a need to state that there is heterogeneity in Spanish, there is a contrastivity in Spanish, there is Uruguayan language/speech; In entries, we consider that there are two types of functioning for contrastivity in DEU: as specificity or as complementarity. The specificity is established when the DEU brings in the definitions specific senses that are not contemplated in the DLE; the complementarity is established when the DEU repeats/reproduces senses of the DLE. Our gesture of interpretation reveals that the contrastive, in the DEU, does not work only in one way; there are differences, there are similarities, and a space of visibility is opened to the Spanish Language of Uruguay.